The Concept of Secularization in Empirical Research - Shiner, Larry E. (Journal for the scientific study of religion, 1967)
In both empirical research and interpretation today there is a total lack of agreement as to what secularization is and how to measure it. The present paper tries to bring the concept of secularization into focus by considering 1) the history of the term, 2) six types of usage today and their application in selected examples of research, 3) a critique of these forms of secularization concept as analytical tools, and 4) a critique of the secular-religious polarity. It is concluded that the term secularization, because of its polemical past, its extremely varied definitions, and its frequent use as a blanket term to cover several disparate processes, should either be abandoned or be explicitly recognized as a comprehensive term covering three complementary but distinct processes, desacralization, differentiation and transposition.